A whole genome screen for linkage in Turkish multiple sclerosis - Eraksoy, M.; Kurtuncu, M.; Akman-Demir, G.; Kilinc, M.; Gedizlioglu, M.; Mirza, M.; Zorlu, Y. (Elsevier, 2003)
Factors exerting recessive effects on susceptibility to complex traits are expected to be over-represented in communities having a higher frequency of consanguineous marriage. Multiple sclerosis, a typical complex trait, is relatively common in Turkey where cultural factors also determine a high rate of consanguineous marriage. Previous genetic studies of multiple sclerosis in Turkey have been confined to the search for associations with candidate genes. In order to exploit the special genetic features of the Turkish population, we performed a whole genome screen for linkage in 43 Turkish multiplex families employing 392 microsatellite markers. Two genomic regions where maximum lod score (MLS) values were suggestive of linkage were identified (chromosomes 13q and 18q23) along with a further 14 regions of potential linkage. Parametric analysis of these data using a recessive model, appropriate for populations with a high frequency of consanguinity, increased the LOD scores in four regions. © 2003 Elsevier B.V. All rights reserved.
Keywords: Genome screen; Linkage; Multiple sclerosis; Turkey